Produção de biodiesel via hidroesterificação: uma revisão sistemática - Silva, Ingrid Augusto Caneca da (2021)
Currently the production of biodiesel is carried out predominantly by the transesterification reaction via alkaline catalysis, but this equilibrium reaction presents some problems such as the use of only high quality raw material, requiring a pre treatment before the main reaction if it is not within the required parameters and the occurrence of parallel reactions such as saponification, which cause several financial losses and lead to an increase in the final price of the biofuel. Therefore, new production technologies have been developed, enabling the use of low quality raw material such as residual oils and fats, without the need for a treatment step prior to the main reaction, e.g., production route via hydroesterification. Thus, the aim of this work is to carry out a systematic review of the literature on the production of biodiesel by hydroesterification using urban waste oils as raw material. The applied methodology was based on a selection filter restricted to scientific articles in Portuguese and English, in the Scopus and Web of Science databases. As a result, 33 articles were obtained, all in English, of which 6 went through all selection filters and 1 was selected separately, in order to add knowledge on the subject. It can be observed that more than 85% of the selected articles are of national origin, thus demonstrating the pioneering Brazilian scientific production on the subject and that the lipase was the most used as a catalyst (biocatalysis) for the biodiesel production via hydroesterification process.